2020
DOI: 10.1089/scd.2019.0098
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem Cell-Derived Non-Cardiomyocytes Modulate Cardiac Electrophysiological Maturation Through Connexin 43-Mediated Cell-Cell Interactions

Abstract: The functional maturation status of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) has a notable impact upon their use in pharmacological studies, disease modeling, and therapeutic applications. Non-cardiomyocytes (non-CMs) produced in the differentiation process have previously been identified as having an extrinsic influence upon hiPSC-CM development, yet the underlying mechanisms are not fully understood. Herein, we aimed to modulate electrophysiological properties of hiPSC-CMs withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
(64 reference statements)
3
18
0
Order By: Relevance
“…This strongly suggests a crosstalk between cFBs and hiPSC-CMs where the presence of cFBs influences the mechanoresponsiveness of hiPSC-CMs. This is in line with previous studies that showed that the number and activation state of cFBs modulated the electromechanical functioning of hiPSC-CMs [48][49][50][51]. Further studies should be directed to investigating the mechanisms that trigger the strain-induced reorientation response in the CM-cFB co-culture.…”
Section: Discussionsupporting
confidence: 89%
“…This strongly suggests a crosstalk between cFBs and hiPSC-CMs where the presence of cFBs influences the mechanoresponsiveness of hiPSC-CMs. This is in line with previous studies that showed that the number and activation state of cFBs modulated the electromechanical functioning of hiPSC-CMs [48][49][50][51]. Further studies should be directed to investigating the mechanisms that trigger the strain-induced reorientation response in the CM-cFB co-culture.…”
Section: Discussionsupporting
confidence: 89%
“…At the end of our differentiation process, some cells were not positive for cTnT and therefore were not CMs. Previous studies have shown that these non-CMs at the end of the differentiation process are primary cardiac-like fibroblasts together with a small portion of non-differentiated hPSCs 41 . hPSC-derived CMs exhibit distinct metabolism from other hPSC-derived non-CMs 42 .…”
Section: Discussionmentioning
confidence: 99%
“…At the end of our differentiation process, some cells were not positive for cTnT and therefore were not CMs. Previous studies have shown that these non-CMs at the end of the differentiation process are primary cardiac-like fibroblasts together with a small portion of non-differentiated hPSCs 35 . hPSC-derived CMs exhibit distinct metabolism from other hPSC-derived non-CMs 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Co-culture of cardiac fibroblasts and CMs can induce fibroblast glycolytic activity and lactate secretion from fibroblasts 37 . Co-culture of cardiac fibroblasts and CMs also promotes a more mature phenotype in CMs along with increased reliance on oxidative phosphorylation 35 . Similarly, differences in NAD(P)H lifetime variables between CMs and non-CMs on day 8 (Figure 4h) are consistent with decreased glycolytic activity in the CMs (Figure S8).…”
Section: Discussionmentioning
confidence: 99%